CLASSE, GÊNERO, RAÇA E OS ENTRAVES AO ENFRENTAMENTO DO TRABALHO DOMÉSTICO DE MENINAS: análise do Redesenho do Programa de Erradicação do Trabalho Infantil no Maranhão. - SILVA, Carla Cecília Serrão (2021)
The object of this thesis is to face the domestic work of girls through the Ações Estratégicas de Prevenção do Trabalho Infantil, taking class, race and gender as main obstacles to such an attempt. The perspective assumed in the discussion of the text is that any action aimed at tackling the domestic work of girls in the homes of others must presuppose approaches on the conditions of class, gender, and race, since it’s understood that overcoming the condition of exploitation to which they are subjected requires changes in the subjective structures of society, an intestinal decolonization, rather than an institutionally conformed legal apparatus. Given this perspective, the categories of gender and race are treated as social markers of the inequalities that support the domestic work of girls and produce the naturalization of the violation of rights, while they prevent public agents involved in the implementation of policies that confront child labor. perceive the illegality present in the practice of keeping girls as workers in the homes of others. In analyzing how much gender inequalities contribute to the persistence of girls' work as domestic servants, the approach adopted looks at the elements associated with gender relations, the sexual division of labor and the idea of unproductive work constituted from a patriarchal and sexist culture. In the same line of analysis, race is presented as a human classification mechanism, a practice that since the period of Brazilian colonization has been useful to the interests of control and marginalization of black people, whose stereotyped and segregated identities reinforce inferiority, subjection and, consequently, the exploitation of female child labor in domestic work. With a view to confirming the assumptions above, the text is also composed of historical, political and cultural, as well as statistical data that reveal the most recent picture of the worst forms of child labor in Brazil and Maranhão, which justify the Redesenho do Programa de Eradicação do Trabalho Infantil through strategic actions aimed at confronting the work of children and adolescents in the 70 municipalities in Maranhão with the highest worst forms of child labor, among which is domestic work for girls.